Arranjo produtivo local: O caso da piscicutura na região de dourados/ms - Takahashi, Fabiana [UNESP]; Leão, Flávia Rover; Campeão, Patrícia (My University, 2008)
This study uses the concepts of economic development from the perspective of local production arrangements (APL), with a focus on local development, and aims to analyze the psciculture activity in Dourados region, in Mato Grosso do Sul. APLs are known as the productive matrix activities based on the economy of proximity and is represented mainly by small and medium-sized companies which represent specific forms of production organization. These are integrated to the territory and are capable of autonomous development, based on the action as a main territorial propulsion development. The region of Dourados, located in the State of Mato Grosso do Sul, stands out in the national market for the production of grains and the creation of cattle and chickens, with the presence of multinationals around. Parallel to these activities, psiculture has been highlighted in the state as an economic activity with high development potential and an alternative income for small landowners in the region, which concentrates more than 60% of the pool for the activity of psiculture in the State of Mato Grosso do Sul.
Productive arrangement spot: The case of pisciculture in dourados region, ms
Keywords: Local development; Productive arrangement spot; Psciculture